A lightweight key management scheme based on an Adelson‐Velskii and Landis tree and elliptic curve cryptography for wireless sensor networks. (24th October 2013) - Boumerzoug, Hayette; Amar Bensaber, Boucif; Biskri, Ismail
Abstract: Wireless sensor networks are increasingly used in most varied fields such as environment, health, and military. Often, information transmitted on these networks requires encryption to maintain confidentiality, integrity, and non‐repudiation. But encryption techniques used to encrypt data on wired networks are not suitable for sensor networks that consist of small nodes equipped with limited resources. In this paper; we propose a security method for wireless sensor networks that provides good protection while taking into account the limited resources of the sensors. This method is based on an effective key management scheme with a minimum storage of keys. It is based on the combination and improvement of two approaches already proposed by the research community: cryptography based on elliptic curves and key management based on an Adelson‐Velskii and Landis tree. Compared with RECC 'a routing‐driven elliptic curve cryptography based key management scheme for heterogeneous sensor networks' and CECKM 'high‐effect key management associated with secure data transmission approaches in sensor networks using a hierarchical‐based cluster elliptic curve key agreement', two methods based on Diffie–Hellman elliptic curve cryptography method, our method reduces energy consumption, storage memory, and extends the lifetime of the sensor network. Our simulation results illustrate that our approach saves significant time and memory and reduces the number of exchanged packets during keys installation phase. Also, it requires fewer processing operations and maintains the scalability of the network. Concurrency and Computation: Practice and Experience, 2013.© 2013 Wiley Periodicals, Inc.